Public Value Of Business Legality Number (NIB) Through Online Single Submission (OSS) System - Anita Anita; Salsa Fitriyah; Sri Wulandari; Iskandar Zulkarnaen (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze the Public Value of Business Legality Business Identification Number (NIB) through the Online Single Submission (OSS) System, Obstacles or Constraints that often occur in the registration of Business Legality Business Identification Number (NIB) through the Online Single Submission (OSS) System, and also to analyze Efforts made to overcome obstacles or constraints in Business Legality Business Identification Number (NIB) through the Online Single Submission (OSS) System in Cirebon Regency. The analysis method used in this research is a qualitative descriptive analysis method. The results showed that the Public Value of Business Legality Business Identification Number (NIB) through the Online Single Submission System was still not formed because only two aspects of the Strategy Trilogy (a strategic triangle) were effective, namely Legitimacy and Support and Subtantively valuable. Meanwhile, the Operational Capabilities aspect is still not effective.